Medicine on the periphery : public health in Yucatán, Mexico, 1870-1960 - Sowell, David, 1952- (Lanham, Maryland : Lexington Books, 2015)
Medicine on the Periphery traces the development of Yucatán's medical institutions, public health programs, healers, and changing disease environment from the 1870s through 1960. The biomedicalization of Yucatán's public health system is analyzed within the Atlantic medical community and the emerging revolutionary state of central Mexico.
Public health and the making of modern Yucatán -- Institutionalizing biomedicine -- Medical communities -- Disease and public health campaigns -- Public health and the revolutionary state -- The biomedicalization of Yucatán.
Includes bibliographical references (pages 175-197) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Public health -- Mexico -- Yucatán (State) -- History; Medical care -- Mexico -- Yucatán (State) -- History; Politics, Practical; Social ecology; Public Health -- history; Delivery of Health Care -- history; History, 19th Century; History, 20th Century; Politics; Social Environment; Mexico; Santé publique -- Mexique -- Yucatán (État) -- Histoire; Médecine -- Histoire -- 19e siècle.; Médecine -- Histoire -- 20e siècle.; Politique; Écologie sociale; Soins médicaux -- Mexique -- Yucatán (État) -- Histoire; politics; human ecology; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Medical care; Public health; Mexico; History